Integrated Spatial Governance for Sustainable Tourims in Bali - Wiryawan, I Wayan Gde; Julianti, Lis; Permadhi, Putu Lantika Oka; Abdullah, Nurhidayah binti (Lembaga Contrarius Indonesia, 2026)
Tourism development in Bali increasingly confronts structural challenges generated by the persistent tension between economic growth imperatives, environmental sustainability, and the preservation of local cultural identity. However Bali’s Spatial Planning Regulation (RTRW) 2023–2043 integrates the Tri Hita Karana philosophy and the principle of “one island, one plan, one management,” its implementation remains constrained by fragmented inter-agency coordination, limited law enforcement capacity, and a development orientation that privileges economic interests over socio-ecological balance. In response, this study examines how an integrated spatial governance framework can harmonize national legal instruments with local wisdom to support sustainable tourism development in Bali. Using a normative juridical research method, the study employs conceptual analysis, statutory review, and comparative legal approaches. The findings demonstrate, first, that local regulatory instruments, particularly awig-awig and community-based zoning mechanisms, contribute significantly to maintaining spatial equilibrium and protect cultural identity and environmental values at the community level. Second, the study finds that the effectiveness of these local instruments remains limited by inadequate formal regulatory recognition and weak alignment with central government mechanisms, including risk-based business licensing systems and spatial conformity approval processes. Third, comparative analysis of Thailand’s sustainable tourism governance, especially the Designated Areas for Sustainable Tourism Administration (DASTA) model, reveals that effective spatial governance depends on robust multi-actor collaboration and institutional coherence that formally integrates local governance structures within designated tourism areas.